Dealing with opposites as a mechanism of change in art therapy in personality disorders: A mixed methods study - Haeyen, Suzanne; Ziskoven, Johannes; Heijman, Jackie; Joosten, Evelien (Frontiers in Psychology, 2022)
Introduction Personality disorders can be characterized by emotion regulation problems, difficulties in self-regulation and by dichotomous, black-and-white thinking. Dealing with opposites as a mechanism of change used by art therapists might be beneficial for people diagnosed with a personality disorder. This study examined the overall question if and in what way dealing with opposites in art therapy is a mechanism of change in achieving personal therapeutic goals. Method A convergent parallel mixed-methods pilot study was performed among patients with a personality disorder (N = 32). Participants received four sessions of art therapy focused on opposites. They completed questionnaires on emotion regulation, positive and negative affect and sense of emotional balance before and after each session. Additionally, they completed a questionnaire on self-expression before and after the four sessions. Furthermore, 10 interviews (eight patients/two therapists) were conducted. Results Quantitative results comparing baseline versus after the four sessions showed a significant change indicating that there might be a positive change regarding self-expression and emotion regulation (t = −2.45, p = 0.02, ES d = 0.30). A significant change was measured in acceptance of emotional responses (Z = −2.66, p = 0.01) and the state of emotion was rated as more balanced (Z = −2.19, p = 0.03). No further significant changes were found. Qualitative results showed that using opposites in art therapy often helped to gain insight, self-exploration and self-awareness and could facilitate confrontation as well as acceptance although sometimes it was (too) confronting. Discussion Integration of conflicting emotions, behaviors, and thoughts were promoted by the explicit use of opposites and supporting coherent representation. Practice based recommendations are therefore to make more explicit use of dealing with opposites as a theme in art therapy. Also, we recommend more research on different mechanisms of change to refine the theory of change that provides an underpinning rationale and structure for art therapy. The results of this research should be regarded as exploratory given the small sample size and limited amount of therapy sessions.